Proses Inaktivasi Enzim Gaultherase Melalui Mixed-Drying Extraction untuk Pengambilan Gaultherin Sebagai Antikanker - Priyono Kusumo (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Research destination is to determine the production process of gaultherin from gandapura in optimum manner through gaultherase enzyme inactivation techniques with mixed-drying extraction technology. Research activities include: gaultherin productivity studies and optimization of process parameters. Efforts to improve gaultherin productivity including the effect of addition of drying agent (magnesium sulfate, sodium sulfate, calcium chloride, and calcium sulfate). Optimization study was conducted using a factorial design 2n. Determination of influential variables by using normal probability plots, after the calculation of the main effects and interaction calculations. During the process, measure the content of gaultherin, methyl salicylate, salicylic acid using a spectrophotometer or HPLC-MS. The results show that increasing the concentration of drying agent and ethanol causes greater gaultherin acquisition, especially with the addition of calcium chloride. Results stated that the variable of mixed-drying process extraction for enzyme inactivation of gaultherase which most influential is the pH and concentration of alcohol. The greater pH of extraction, will enhance the result of the active compound gaultherin. The greater solvent concentration, gaultherin that extracted increasing. Optimum Gaultherin production achieved at a concentration 90% of ethanol with the acquisition of active compound 13.10% .